Relations Of The Mother's Motivation About The Behaviour Of The Clean And Healthy Life With The Diarrhoea Incident To Child - Nurwijayanti; Taunais, Maria Herlina (Journal of Global Research in Public Health, 2020)
Diarrhoea was still being the problem of the health of the community in Indonesia, because very dangerous and could cause the death to pre-schoolers that the incident figure relative still was high. Generally, the community connected with pollution of the bacteria that was impressed dirty. The cause of diarrhoea of many of his styles, from the bacterial infection or the virus, did not compare ate, pollution of the bacteria, pollution of food by the substance that was dangerous to the sensitivity against the carbohydrate or fat as well as protein. The aim of this research of knowing relations of the mother's knowledge about the behaviour of the clean and healthy life with the diarrhoea incident in the age child 1-5 years in Kediri cities. This research used the research plan with the approach cross sectional, with pupolasi him was all the mothers who had the diarrhoea child in the Kediri City. With accidental sampling Sample this research was some mothers who had the diarrhoea child in the Kediri cities from januari 17 to february 23 2020 totalling 119 respondents. The analysis data and was presented in the table. To know relations 2 variables were used by the Chi statistical test square that was counted with SPSS with the value = 0.05. From results of the research could be known that the respondent who had good motivation 55 respondents (46.66 %), was 44 respondents (36.66%), motivations not all that 20 respondents (16.66%), and the high diarrhoea incident 67 respondents (56.66%), low diarrhoea 52 respondents (43.33%). Results of the statistical test were obtained = 0.015, that meaning that thought ρ < α. From these results could be concluded that there is relations of the mother's knowledge about the behaviour of the clean and healthy life with the diarrhoea incident in the age child 1-5 years in the central health of community Pesantren II in the Kediri City. The child was the nation younger generation that could build this nation to the side of that was better. If the child was sick then will influence the growth and the physical development, psychological, the intellectual, and spiritual.